Cholesterol Stimulates the Transient Receptor Potential Melastatin 4 Channel in mpkCCDc14 Cells - Cai, Yong-Xu; Zhang, Bao-Long; Yu, Miao; Yang, Yan-Chao; Ao, Xue; Zhu, Di; Wang, Qiu-Shi; Lou, Jie; Liang, Chen; Tang, Liang-Liang; Wu, Ming-Ming; Zhang, Zhi-Ren; et al. (Frontiers in Pharmacology, 2021)
We have shown that cholesterol regulates the activity of ion channels in mouse cortical collecting duct (CCD) mpkCCDc14 cells and that the transient receptor potential melastatin 4 (TRPM4) channel is expressed in these cells. However, whether TRPM4 channel is regulated by cholesterol remains unclear. Here, we performed inside-out patch-clamp experiments and found that inhibition of cholesterol biosynthesis by lovastatin significantly decreased, whereas enrichment of cholesterol with exogenous cholesterol significantly increased, TRPM4 channel open probability (Po) by regulating its sensitivity to Ca2+ in mpkCCDc14 cells. In addition, inside-out patch-clamp data show that acute depletion of cholesterol in the membrane inner leaflet by methyl-β-cyclodextrin (MβCD) significantly reduced TRPM4 Po, which was reversed by exogenous cholesterol. Moreover, immunofluorescence microscopy, Western blot, cell-surface biotinylation, and patch clamp analysis show that neither inhibition of intracellular cholesterol biosynthesis with lovastatin nor application of exogenous cholesterol had effect on TRPM4 channel protein abundance in the plasma membrane of mpkCCDc14 cells. Sucrose density gradient centrifugation studies demonstrate that TRPM4 was mainly located in cholesterol-rich lipid rafts. Lipid-protein overlay experiments show that TRPM4 directly interacted with several anionic phospholipids, including PI(4,5)P2. Depletion of PI(4,5)P2 with either wortmannin or PGE2 abrogated the stimulatory effects of exogenous cholesterol on TRPM4 activity, whereas exogenous PI(4,5)P2 (diC8-PI(4,5)P2, a water-soluble analog) increased the effects. These results suggest that cholesterol stimulates TRPM4 via a PI(4,5)P2-dependent mechanism.